Insights into subunit interactions in the Sulfolobus acidocaldarius archaellum cytoplasmic complex. (18th October 2013) - Banerjee, Ankan; Neiner, Tomasz; Tripp, Patrick; Albers, Sonja‐Verena
<x xml:space="preserve">Abstract</x> Archaella are the archaeal motility structure that is the functional pendant of the bacterial flagellum but is assembled by a mechanism similar to that for type IV pili. Recently, it was shown by Banerjee et al. that FlaX, a crenarchaeal archaellum subunit from Sulfolobus acidocaldarius, forms a ring‐like oligomer, and it was proposed that this ring may act as a static platform for torque generation in archaellum rotation [Banerjee A et al. (2012) J Biol Chem 287, 43322–43330]. Moreover, the hexameric crystal structure of FlaI was solved, and its dual function in the assembly and the rotation of the archaellum was demonstrated [Reindl S et al. (2013) Mol Cell 49, 1069–1082]. In this study, we show by biochemical and biophysical techniques that FlaX from S. acidocaldarius acts as a cytoplasmic scaffold in archaellum assembly, as it interacts with FlaI as well as with the recA family protein FlaH, the only cytoplasmic components of the archaellum. Interaction studies using various truncated versions of FlaI demonstrated that its N‐ and C‐termini interact with FlaX. Moreover, using microscale thermophoresis, we show that FlaI, FlaX and FlaH interact with high affinities in the nanomolar range. Therefore, we propose that these three proteins form the cytoplasmic motor complex of the archaellum. Structured digital abstract FlaH and FlaI bind by mst (View interaction) FlaXc physically interacts with FlaI by pull down (1, 2) FlaI and FlaXc bind by mst (1, 2) FlaI binds to FlaXc by pull down (View interaction)